Uncertainty Modelling in Information Management and Decision Making. - Kahraman, Cengiz (Journal of Enterprise Information Management: Volume 27, Issue 3., 2014)
This ebook incorporates excellent 'quality' submissions that focus on providing a mixture of theoretical and practical contributions. The research work presented in these papers highlights that social media are playing a rapidly expanding role in both companies and in teaching and learning. The aim of this ebook is to provide a broad understanding of the significance that uncertainty modelling, in the context of managing information resources and decision-making process, plays. The techniques for uncertainty modelling and analysis in engineering presents appropriate analytical and useful tools.